'One Big Playground for Kids': A Contextual Appraisal of Some 1970s Photographs of Children Hanging Out on a Post-Second-World-War British Council Estate. (3rd July 2018) - Waites, Ian
ABSTRACT: This article gives a broad assessment of a selection of photographs taken in the early 1970s of children on a post-Second-World-War British council estate in Gainsborough, Lincolnshire. As one of the cornerstones of postwar social reconstruction in Britain, the provision and design of new public housing often had the well-being of the future citizen – the child – in mind, and the photography of these estates at the time often included children as a way to promote a sense of well-being and community. This article offers a reading of these photographs as a representation of the child's day-to-day life in this particular environment, and to present an understanding of how the planning and layout of the estate was intended to function as a crucial influence on the development of the children who lived there.